Clinical efficacy and safety of a water‐soluble micellar paclitaxel (Paccal Vet) in canine mastocytomas. (27th November 2012) - Rivera, P.; Åkerlund‐Denneberg, N.; Bergvall, K.; Kessler, M.; Rowe, A.; Willmann, M.; Persson, G.; Kastengren Fröberg, G.; Westberg, S.; von, H.
<x xml:space="preserve">Abstract</x> Objective To determine the clinical efficacy and safety of a cremophor‐free formulation of paclitaxel (Paccal Vet, Oasmia Pharmaceuticals) in dogs with mast cell tumours. Methods Paccal Vet was administered at a median dose of 145 (range, 135 to 150) mg/m2intravenously once every 21 days for three cycles to 29 dogs with macroscopic grade 2 or 3 mast cell tumour. Efficacy was assessed by tumour response (Response Evaluation Criteria in Solid Tumours version 1.0) and performance status score. Progression‐free survival, quality of life and safety/adverse events were also evaluated. Clinical safety was assessed by clinicopathological analyses and recording of adverse events. Results Complete or partial response was observed in 59% of dogs. Performance status score remained constant or improved for 20 dogs and decreased by one grade for 9 dogs. Median time to progression was 247 (range, 42 to 268) days. Expected, transient frequently subclinical adverse events (primarily grade 3/4 neutropenia and grade 1/2 leukopenia) were observed in the majority of dogs. Nine dogs were euthanased and one dog died due to disease progression. Clinical Significance Paccal Vet appears to be a clinically safe and effective treatment for canine mast cell tumours. Further controlled confirmatory investigation is warranted.